G50(P) Transition from paediatric to adult services in epidermolysis bullosa (EB). (7th April 2014) - Robertson, SJ; Foster, L; Martinez, AE; Mellerio, JE
Abstract : Aims: We describe our specialist centre experience in the transition of young adult patients with severe types of EB from paediatric to adult health services. Methods: EB is a rare, complex inherited disease characterised by mechanical fragility of the skin and mucous membranes, and other systemic involvement. Children with EB have chronic health care needs and develop long-standing relationships and trust with staff and services within their paediatric care setting. The process of transition to adult services may be a stressful and frightening experience as they establish new relationships with the adult team. In particular, severe forms of EB associated with early development of aggressive squamous cell carcinoma (SCC), necessitate a focus on surveillance from the early teens, which must continue throughout adulthood. With this in mind, we devised guidelines for young adult patients with severe forms of EB to prepare them for transition feeling supported, fully informed and in control. Results: The transfer of patients from paediatric to adult EB centres is a planned and co-ordinated process, the timing of which takes into consideration the individual needs and wishes of the young person and their parents. Discussion about transition to adult EB services begins when the patient is aged 12–13 years. There is a choice of the adult service they wish to transition to, depending on geographic location and preference. A visit to one or both of the adult centres is arranged in the year prior to planned transition. An EB nurse from the adult centre attends a home visit along with the patient's usual paediatric EB nurse before transition to allow a personal introduction. Once transitioned, the patient's usual paediatric EB nurse attends their first clinic appointment at the adult centre. Conclusion: Transition between paediatric and adult EB services relies on close liaison between centres, early discussion and involvement of the EB nurses. Through planning and preparation, this process, which may include discussion of difficult areas such as early SCC development, can be managed sensitively and smoothly to ensure ongoing complex health care needs are delivered seamlessly.